Nick Ervinck : works : GNI_RI_2022 - Sint-Jacobskerk (Ghent, Belgium); Decreus, Freddy, 1949-; Ervinck, Nick, 1981-; Hübl, Michael; Wood, Jon ([Antwerp] : Hannibal, 2022)
As an artist, Nick Ervinck (°1981) is mainly interested in the field of tension between nature and culture, between tradition and innovation. In his work he tries to push the boundaries of digital possibilities, always with respect for the (art) historical heritage. Nick Ervinck - Works, GNI_RI_2022 brings together Ervinck's well-known monumental sculptures and 3D prints, as well as drawings, ceramics and new work in brick and bronze. With a text contribution by writer and curator Jon Wood, a specialist in modern and contemporary sculpture who led the research program of the Henry Moore Institute for many years. Freddy Decreus, professor emeritus at Ghent University, and Michael Hübl also wrote a text contribution. Exhibition: St. Jacobskerk, Ghent, Belgium (23.05.-24.07.2022)
Een woordje uitleg bij de sculpturen van Nick Ervinck.
Als kunstenaar is Nick Ervinck (°1981) vooral geïnteresseerd in het spanningsveld tussen natuur en cultuur, tussen traditie en innovatie. In zijn werk tracht hij de grenzen van de digitale mogelijkheden te verleggen, steeds met respect voor het (kunst)historische erfgoed. Nick Ervinck - Works, GNI_RI_2022 bundelt Ervincks gekende monumentale sculpturen en 3D-prints, alsook tekeningen, keramiek en nieuw werk in baksteen en brons. Met een tekstbijdrage van schrijver en curator Jon Wood, specialist in moderne en hedendaagse beeldhouwkunst die jarenlang het onderzoeksprogramma van het Henry Moore Instituut leidde. Ook Freddy Decreus, professor emeritus aan de Universiteit Gent, en Michael Hübl schreven een tekstbijdrage.
Catalog of an exhibition held at St. Jacobskerk, Ghent, Belgium, from May 23 - July 24, 2022.
Includes bibliographical references.
Tentoonstelling
In Dutch and English.
Keywords: Ervinck, Nick, -- 1981-.